2022
DOI: 10.1371/journal.pntd.0010754
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection and characterisation of the first Japanese encephalitis virus belonging to genotype IV acquired in Australia

Abstract: Background A fatal case of Japanese encephalitis (JE) occurred in a resident of the Tiwi Islands, in the Northern Territory of Australia in February 2021, preceding the large JE outbreak in south-eastern Australia in 2022. This study reports the detection, whole genome sequencing and analysis of the virus responsible (designated JEV/Australia/NT_Tiwi Islands/2021). Methods Reverse transcription quantitative PCR (RT-qPCR) testing was performed on post-mortem brain specimens using a range of JE virus (JEV)-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 68 publications
0
44
0
Order By: Relevance
“…A phylogenetic tree of JEV was constructed using the nucleotide sequence of the E gene of the GI–GV JEV strains ( Figure 1 ). Strain 19CxBa-83-Cv was clustered in the GIV and showed higher homology to the Bali2019 strain isolated from an Australian JE patient infected in Bali in 2019, compared to the strains JEV/Aus/NT_Tiwi Islands/2021 (Hu_Tiwi 2021; OM867669) and sw-22-00722-11 (ON624132) identified in Australia in 2021 and 2022, respectively [ 30 , 31 , 38 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A phylogenetic tree of JEV was constructed using the nucleotide sequence of the E gene of the GI–GV JEV strains ( Figure 1 ). Strain 19CxBa-83-Cv was clustered in the GIV and showed higher homology to the Bali2019 strain isolated from an Australian JE patient infected in Bali in 2019, compared to the strains JEV/Aus/NT_Tiwi Islands/2021 (Hu_Tiwi 2021; OM867669) and sw-22-00722-11 (ON624132) identified in Australia in 2021 and 2022, respectively [ 30 , 31 , 38 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Genetic analysis of the JEV isolates from mosquitoes and pigs indicated that the isolates in 1998 also belonged to GII, whereas the isolate from Badu in the Torres Strait Islands in 2004 belonged to GI [ 36 , 37 ]. A JE patient who was thought to be infected with GIV JEV in the Tiwi islands in northern Australia was confirmed as infected in Australia in 2021 following a 20-year absence of JE [ 38 , 39 , 40 ]. In 2022, JEV was widespread in Australia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A fatal case of JE occurred in March 2021 in an inhabitant from the Tiwi Islands. 43,44 Sequence studies confirmed that it was JEV belonging to genotype IV, the first time this genotype was acquired outside Indonesia. It was also the second known fatal human infection due to GIV, the first having been reported in an Australian tourist to Bali.…”
Section: The Re-emergence Of Japanese Encephalitis Virus In Australiamentioning
confidence: 87%
“…We present a simple yet robust workflow for the mNGS of RNA from clinical respiratory samples. Our RAPIDprep assay has been designed specifically as a rapid response tool, and has proven to be effective in novel disease investigations, including identifying the first cases of emergent Japanese encephalitis virus during the 2021-22 outbreak in south-eastern Australia [42,43], and characterising the first cases of COVID-19 in NSW [33]. The assay has also been used to investigate non-human diseases, and was critical to the genome recovery of a novel Hendra virus variant detected initially from a fatal equine infection by pan-paramyxovirus RT-PCR [1].…”
Section: Discussionmentioning
confidence: 99%